Radiation Dose Optimization Techniques in CT-Scan for Patient Safety in Radiology Departments in Tripoli, Libya. - Professor: Ali Masoud El-Mansuri (Aljameai, 2025)
Abstract:  In response to concerns about the increasing use of radiation exposure from the growing CT scan use and associated risks. This study aimed was to assess and sought to optimize radiation dose protocols in CT scans across radiology departments in Tripoli, Libya, to improve patient safety. The data from 140 patients who underwent brain, chest, abdomen-pelvis, and par nasal sinus (PNS) CT scans from two Central Hospital revealed statistically significant variations in doses for different procedures.  The analysis included parameters such as tube current (MAS), tube voltage (KVP), computed tomography dose index (CTDI), and dose-length product (DLP). Statistical analyses, including ANOVA and Scheffe’s test, revealed significant dose variations in radiation doses across different scan types and hospitals. Some effective radiation doses were analyzed using anatomical conversion factors, for instance,  brain CT scans averaged 1.53 MSV while PNS scans averaged 2.62 MSV. This research study emphasized the importance of complying with the ALARA protocols and recommended protocol adjustments, such as adjusting tube current and optimizing scan length  to minimize radiation exposure without compromising diagnostic quality.المستخلص:     أدى الانتشار المتزايد لاستخدام التصوير المقطعي المحوسب (CT) في الفحوصات التشخيصية إلى بروز مخاوف متزايدة بشأن مخاطر جرعات الإشعاع التي قد يتعرض لها المريض, و ما يمكن أن يترتب عليها من اثار صحية خطيرة. أن الهدف من هذه الدراسة البحثية هو لتقييم البروتوكولات المستخدمة في جرعات الاشعاع أثناء التصوير المقطعي خلال الفحوصات الطبية التي تجرى على المرضى في مدينة طرابلس،  ليبيا، مع التركيز على اهمية تحسين هذه البروتوكولات من اجل رفع مستوى السلامة الاشعاعية للمرضى. أجريت هذه الدراسة على 140 مريضًا خضعوا لفحوصات مقطعية  شملت الدماغ، و البطن و الصدر و الحوض و الجيوب الأنفية (PNS) في مستشفى طرابلس المركزي و مستشفى معيتيقة العسكري.  و تم تحليل مجموعة من المعايير التقنية من بينها شدة التيار الكهربائي (MAS) و فرق الجهد (KVP) و مؤشر جرعة التصوير المقطعي (CTDI)  ومنتج الطول الجرعة ((DLP .استنادا إلى الاختبارات الإحصائية المستخدمة مثل اختبار ANOVA واختبار Scheffe , فأن نتائج هذه الدراسة أظهرت وجود فروق ذات دلالة إحصائية في مستويات جرعات الإشعاع المختلفة سواء بين انواع الفحوص أو بين هذين المستشفيين. كما تم قياس الجرعات الفعالة باستخدام  معاملات التحويل التشريحية حيث بلغ متوسط الجرعة في فحص الدماغ 1.53 ملي سيفرت، بينما بلغ متوسط جرعة فحص الجيوب الأنفية 2.62 ملي سيفرت. و تؤكد نتائج هذه الدراسة أهمية الالتزام بمبدأ ALARA  القائم على تقليل جرعات الاشعاع ادنى مستوى  دوت الاثير على جودة التصوير المقطعي مع التوصية بتحديث البروتوكولات المعمول بها  بما في ذلك خفض شدة التيار الكهربائي و تحسين و ضبط طول منطقة الفحص  بهدف تقليل التعرض الاشعاعي و تعزيز فعالية التشخيص .